ASSESSING THE COMPETITIVENESS OF "SMART" CITIES OF KAZAKHSTAN: MARKETING ASPECT - Shurenov, N.B.; Bimendiyeva, L.A.; Nathan, Jay (Scientific Journal of Pedagogy and Economics, 2020)
The article considers the issue of introducing the reference standard of “Smart” cities of the Republic of Kazakhstan. The main achievements and problems of the “Smart” cities of the Republic of Kazakhstan are studied in connection with the introduction of the reference standard. Moreover, there were proposed solutions to the mentioned problems employing digital territorial marketing tools and were analyzed methodical recommendations on the creation of “Smart” cities. The directions and indicators of the reference standard of “Smart” cities regarding public life were considered, and its main development trends were determined. This article provides a rating of introducing the reference standard for “Smart” cities of the Republic of Kazakhstan for 2019. As the method of study, we chose the method of analysis and synthesis, as this is an integral element for the fundamental analysis of the introduction of the standard in smart cities. Using the method of analysis and synthesis, we determined the rating of “Smart” cities of the Republic of Kazakhstan, thus we can calculate the average percentage of the level of implementation of digitization in the areas of public life. In connection with a high or low indicator in a certain area of public life, the determination of the most effective and attractive directions for the implementation of digitization has become possible for the City Administration thanks to marketing analysis.